Election campaign and issues agenda in Malaysian politicians’ Facebook and Instagram accounts - Mohamed, Shafizan; Abdul Manan, Kamaruzzaman (2018)
This study investigates how politicians use Instagram and Facebook as political communication during the 14th general election. The objectives of this study are to explore the politicians' usage pattern, issues highlighted and the type of posting when using Facebook and Instagram. The study found that the politicians actively used Instagram and Facebook in their campaign and issues related to the election were the most popularly communicated by the politicians. In addition, politician candidate like to post still images of their campaign activities and use live streaming to broadcast their campaign speech.